THE INFLUENCE OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT PEGADAIAN RAGIONAL OFFICE REGION III AND PALEMBANG BRANCH - Oktaria, Pesta; Widiyanti, Marlina; Yusuf, Muhammad; Hadjri, Muhammad Ichsan (International Journal of Social Service and Research, 2024)
This study was conducted to determine the impact of leadership style and work motivation on employee performance at PT Pegadaian Ragional Regional Office III and Palembang Branch. The data used in this study is primary data, collected directly from employees through structured questionnaires that measure variables such as leadership style, work motivation, and employee performance. A descriptive and inferential approach was employed to analyze the relationships among the study variables. The results showed that leadership style has a positive and significant effect on employees' performance at the regional office level. Work motivation has an important positive effect on employee's performance so that the second hypothesis can be accepted. Leadership styles have a negative effect on the performance of employees at the Regional Office level, while leadership styles and motivational strategies have positive effects on employee performances. The findings of this study offer practical guidance for organizational leaders and HR professionals seeking to optimize workforce performance through tailored leadership and motivation practices, contributing to more effective management strategies within similar corporate and branch-level environments.